Multitarget Compounds for Bipolar Disorder: From Rational Design to Preliminary Pharmacokinetic Evaluation. (29th April 2020) - Di Martino, Rita Maria Concetta; Bottegoni, Giovanni; Seghetti, Francesca; Russo, Debora; Penna, Ilaria; De Simone, Alessio; Ottonello, Giuliana; Mandrup Bertozzi, Sine; Armirotti, Andrea; Bandiera, Tiziano; Belluti, Federica; Cavalli, Andrea
Abstract: Due to the complex and multifactorial nature of bipolar disorder (BD), single‐target drugs have traditionally provided limited relief with no disease‐modifying effects. In line with the polypharmacology paradigm, we attempted to overcome these limitations by devising two series of multitarget‐directed ligands endowed with both a partial agonist profile at dopamine receptor D3 (D3R) and inhibitory activity against glycogen synthase kinase 3 beta (GSK‐3β). These are two structurally unrelated targets that play independent, yet connected, roles in cognition and mood regulation. Two compounds (7 and 10 ) emerged as promising D3R/GSK‐3β multitarget‐directed ligands with nanomolar activity at D3R and low‐micromolar inhibition of GSK‐3β, thereby confirming, albeit preliminarily, the feasibility of our strategy. Furthermore, 7 showed promising drug‐like properties in stability and pharmacokinetic studies. Abstract : Pharma‐co‐operation : Multitarget‐directed ligands combine partial agonist activity at dopamine receptor D3 and inhibitory activity at glycogen synthase kinase 3 beta (GSK‐3β). Thanks to a seamless integration of key pharmacophore features, these compounds could originate a new wave of therapeutic agents for the treatment of bipolar disorder, endowed with a disease‐modifying effect while devoid of severe side effects.